2022
DOI: 10.1002/ptr.7607
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between traditional Chinese medicine‐derived polysaccharides and the gut microbiota: A new perspective to understand traditional Chinese medicine

Abstract: Polysaccharide is a kind of macromolecule polymer composed of monosaccharides connected by glycosidic bonds. Traditional Chinese medicine (TCM), composed of various bioactive ingredients, is usually rich in polysaccharides. In recent years, extensive research on TCM polysaccharides has demonstrated their pharmacological effects. Polysaccharides can hardly be catabolized by enzymes encoded by the human genome but can be degraded to absorbable metabolites by bacteria inhabiting the colon. Hence, the gut microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…Growing evidences revealed that polysaccharides possess complex biological activities and a variety of biological functions involved in antioxidant, antitumor, antiviral, immune regulation activities and so on ( 21 ). Of note, polysaccharides are widely present in TCM and considered as one of the important bioactive ingredients in TCM ( 22 ). Additionally, polysaccharides can be divided into homopolysaccharides and heteropolysaccharides according to the composition of monosaccharides.…”
Section: Characteristics Of Astragalus Polysaccharidementioning
confidence: 99%
“…Growing evidences revealed that polysaccharides possess complex biological activities and a variety of biological functions involved in antioxidant, antitumor, antiviral, immune regulation activities and so on ( 21 ). Of note, polysaccharides are widely present in TCM and considered as one of the important bioactive ingredients in TCM ( 22 ). Additionally, polysaccharides can be divided into homopolysaccharides and heteropolysaccharides according to the composition of monosaccharides.…”
Section: Characteristics Of Astragalus Polysaccharidementioning
confidence: 99%
“…Importantly, SCFAs are recognized as a mediator in gut-brain axis communication to help the recovery of various neurologic diseases, including AD and PD [158]. In addition, TCM polysaccharides modulate the composition of the beneficial and pathogenic bacteria to relieve intestinal dysbiosis due to an unbalanced diet, antibiotic treatment, stress stimuli, or some disease conditions [159].…”
Section: Immunomodulatory Effect Of Tcmmentioning
confidence: 99%
“…In fact, TCM usually exhibits its effects through the gut microbiota [ 22 , 23 , 24 , 25 ]. Studies have demonstrated that TCM can directly alter the diversity and composition of gut microbiota [ 23 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%